The objective of this research was to investigate the genetic and phenotypic correlations for several productive traits on Madura cattle. The results were expected as a fundamental consideration in selection programme. The research was conducted in Bangkalan Madura for a year. Hundred and eighty calves were analysed from 9 sires sampled using stratified random analysis. At the end of the research 3 bulls were sold thus in the final analysis 120 calves from 6 sires were analysed using resemblance - Nasipan Usri; M.P. Rukmana; A. Anang (Media Veteriner, 2001)
The objective of this research was to investigate the genetic and phenotypic correlations for several productive traits on Madura cattle. The results were expected as a fundamental consideration in selection programme. The research was conducted in Bangkalan Madura for a year. Hundred and eighty calves were analysed from 9 sires sampled using stratified random analysis. At the end of the research 3 bulls were sold thus in the final analysis 120 calves from 6 sires were analysed using resemblance between relatives. The results indicated that genetic and phenotypic correlations between birth weight and weaning weight were 0.43±0.31 and 0.32±0.18, respectively. Genetic and phenotypic correlations between birth weight and pre weaning gain were 0.38±0.28 and 0.32±0.18, respectively. Genetic and phenotypic correlations between weaning weight and yearling weight were 0.59±0.11 and 0.31 ±0.27, respectively, and finally genetic and phenotypic correlations between weaning weight and post weaning gain were 0.43±0.13 and 0.47±0.24, respectively. Based on the correlations, a selection will be able to be conducted based on birth and weaning weight.